BMPR2 promotes invasion and metastasis via the RhoA-ROCK-LIMK2 pathway in human osteosarcoma cells - Wang, Shidong (Oncotarget, 2017)
Bone morphogenetic protein receptor 2 (BMPR2) has been identified in several types of cancer. However, its role in osteosarcoma is largely unknown. We systematically investigated the role of BMPR2 in osteosarcoma cell lines, human tissue samples and xenograft models. The relationship between BMPR2 expression and osteosarcoma patients’ survival was investigated by bioinformatics and clinical data. Wound healing assay and transwell assay were used to detect the changes of cell migration and invasion ability after BMPR2 transfection. In addition, downstream phosphoproteins were analyzed by iTRAQ-based phosphoproteomic analysis and verified by western blotting. In vivo, the effects of BMPR2 on the growth, formation and metastasis of 143B cells were observed by orthotopic transplantation of nude mice. Here, we demonstrated that BMPR2 expression was elevated in a majority of osteosarcoma tissues compared with normal bone tissue. Osteosarcoma patients with greater BMPR2 expressing level showed a poor overall survival. The depletion of BMPR2 in 143B cells markedly reduced the invasive capacity in vitro and metastatic potential in vivo. Mechanistically, we found that LIM domain kinase 2 (LIMK2) was phosphorylated and activated by BMPR2 and that this event was crucial for activation of the BMPR2-mediated signal pathway in osteosarcoma cells. Additionally, we demonstrated that BMPR2 could active LIMK2 through the RhoA/ROCK pathway and could also interact with LIMK2 directly. Taken together, our study revealed that BMPR2 functions as a prometastatic oncogene in vitro and in vivo with the activation of the RhoA-ROCK-LIMK2 pathway and may represent a potential therapeutic target for osteosarcoma.